"The land belonged to Nepal but the people belonged to Tibet": Overlapping sovereignties and mobility in the Limi Valley Borderland. Issue 3 (3rd May 2021) - Yeh, Emily T.
ABSTRACT: Recent scholarship on the lived experiences of borderlands has foregrounded and theorized the pervasiveness of anxiety, violence, and lawlessness. While useful, these do not capture all of the ways in which borderland residents relate to diverse constellations of power. This paper examines the China (Tibet Autonomous Region) – Nepal borderland through the case of the Limi Valley, in the northwest corner of Nepal's Humla district. Before 1959, the valley was considered part of Nepalese territory, yet its residents belonged administratively to the Tibetan government, an arrangement at odds with contemporary understandings of state territorial sovereignty. The non-postcolonial state formations of Nepal and China have created their own specific forms of border citizenship and overlapping sovereignties. The article shows how multiple sovereignties can stretch beyond state borders in unexpected ways by tracing how Limi Valley residents negotiate overlapping sovereignties of the Nepali and Chinese states, as well as the non-state sovereignty of the Tibetan government-in-exile. Furthermore, it demonstrates that these in turn overlap with a form of social sovereignty grounded in the community's body of laws, codes, and practices, which are at once a historically sedimented trace of Limi's governance before the nation-state, and a product of navigating political transformations. However, challenges to this social sovereignty, expressed through the idiom of statist law, have recently emerged. Whereas states typically exert sovereign power in borderlands by restricting mobility, some Limi villagers now selectively invoke state sovereignty through law to enable greater mobility.